Risk stratification using sarcopenia status among subjects with metabolic dysfunction‐associated fatty liver disease. Issue 5 (1st August 2021) - Chun, Ho Soo; Kim, Mi Na; Lee, Jae Seung; Lee, Hye Won; Kim, Beom Kyung; Park, Jun Yong; Kim, Do Young; Ahn, Sang Hoon; Kim, Seung Up
Abstract: Background: Sarcopenia is a significant indicator of the severity of non‐alcoholic fatty liver disease. We investigated whether sarcopenia could identify subgroups with different risk of liver fibrosis and atherosclerotic cardiovascular disease (ASCVD) among subjects with metabolic dysfunction‐associated fatty liver disease (MAFLD). Methods: Subjects from the Korea National Health and Nutrition Examination Survey 2008–2011 were selected ( n = 8361). Sarcopenia was defined using the sarcopenia index. Hepatic steatosis was defined as a fatty liver index ≥30. Significant liver fibrosis was defined as a fibrosis‐4 index (FIB‐4) ≥2.67 or the highest quartile of non‐alcoholic fatty liver disease fibrosis score (NFS). High probability of ASCVD was defined as ASCVD risk score >10%. Results: The mean age was 48.5 ± 15.6 years, and 42.6% of subjects were male. The prevalence of MAFLD was 37.3% ( n = 3116 of 8361), and the proportion of sarcopenic subjects was 9.9% among those with MAFLD. After adjusting for confounders, the risk of significant liver fibrosis significantly increased from non‐sarcopenic subjects with MAFLD [odds ratio (OR) = 1.57 by FIB‐4 and 2.13 by NFS] to sarcopenic subjects with MAFLD (OR = 4.51 by FIB‐4 and 5.72 by NFS), compared with subjects without MAFLD (all P < 0.001). The risk for high probability of ASCVD significantly increased from non‐sarcopenic subjects with MAFLD (OR = 1.47) to sarcopenic subjects with MAFLD (OR = 4.08), compared with subjects without MAFLD (all P < 0.001). Conclusions: The risks of significant liver fibrosis and ASCVD differed significantly according to sarcopenic status among subjects with MAFLD. An assessment of sarcopenia might be helpful in risk stratification among subjects with MAFLD.